Chemical Biology Strategies to Study Autophagy - Mishra, Piyush; Ammanathan, Veena; Manjithaya, Ravi (Frontiers in Cell and Developmental Biology, 2018)
Growing amount of evidence in the last two decades highlight that macroautophagy (generally referred to as autophagy) is not only important for cell survival in yeast but also equally indispensable to maintain cellular quality control in higher eukaryotes as well. Importantly, dysfunctional autophagy has been implicated in various pathophysiological conditions such as cell death, cancer, neurodegenerative and other diseases. Therefore, autophagy has emerged as an attractive target for the treatment of various disease conditions in the recent years. Several studies have shown genetic or pharmacological modulation of autophagy to be effective in treating cancer, clearing intracellular aggregates and pathogens. Understanding and controlling the autophagic flux, either through a genetic or pharmacological approach is therefore a highly promising approach and of great scientific interest as spatiotemporal and cell-tissue-organ level autophagy regulation is not clearly understood. Indeed, chemical biology approaches that identify small molecule effectors of autophagy have thus a dual benefit: the modulators act as tools to study and understand the process of autophagy, and may also have therapeutic potential. In this review, we discuss different strategies that have appeared to screen and identify potent small molecule modulators of autophagy.